2008
DOI: 10.1038/ijo.2008.106
|View full text |Cite
|
Sign up to set email alerts
|

Genes and networks expressed in perioperative omental adipose tissue are correlated with weight loss from Roux-en-Y gastric bypass

Abstract: Context: Gastric bypass surgery is the most commonly performed bariatric surgical procedure in the United States. Variable weight loss following this relatively standardized intervention has been reported. To date, a method for reliable profiling of patients who will successfully sustain weight loss for the long term has not been established. In addition, the mechanisms of action in accomplishing major weight loss as well as the explanation for the variable weight loss have not been established. Objective: To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Gene network analysis applied to obesity and caloric restriction, e.g. following bariatric surgery, highlighted the importance of pathways for glycerolipid metabolism (reviewed in [6,7]). Peroxisome proliferator-activated receptor-γ 1 and 2 ( PPAR γ 1 and 2 ) and 11β-hydroxysteroid dehydrogenase type 1 ( 11 β HSD1 ) are among the glycerolipid metabolism-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Gene network analysis applied to obesity and caloric restriction, e.g. following bariatric surgery, highlighted the importance of pathways for glycerolipid metabolism (reviewed in [6,7]). Peroxisome proliferator-activated receptor-γ 1 and 2 ( PPAR γ 1 and 2 ) and 11β-hydroxysteroid dehydrogenase type 1 ( 11 β HSD1 ) are among the glycerolipid metabolism-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these underexpressed genes plays a role in the metabolism of LCFA, and several have already been reported to play a role in obesity. Acyl-coenzyme A oxidase 1 (1.3.3.6) expression in omental fat reportedly predicts weight loss outcome after gastric bypass surgery [54]. DCI (5.3.3.8), grouped with 3-hydroxyacyl-coenzyme A dehydrogenase (1.1.1.35), plays a key role in LCFA degradation (discussed above).…”
Section: Discussionmentioning
confidence: 99%
“…DNA microarray experiments are typically designed to achieve one or several of the following objectives: (1) to identify individual genes (transcripts) whose expression is correlated with a phenotypic trait such as response to treatment, (2) to identify multiple genes that are interactively involved in regulatory networks and mediating biological phenomena or disease pathogenesis, (3) to discover potential molecular targets for drug development, and (4) to identify molecular markers that can be used as tools for disease diagnosis and prognosis or as predictors of clinical outcomes. Regardless of the purpose of a microarray study, there is one common underlying assumption—the primary end point of the study is associated with the expression levels of a number of genes.…”
Section: Expectations Of Gene Expression Profiling Studiesmentioning
confidence: 99%
“…Regardless of the purpose of a microarray study, there is one common underlying assumption—the primary end point of the study is associated with the expression levels of a number of genes. For example, Kim et al profiled genes from perioperative adipose tissue whose expression was associated with weight loss outcome following Roux-en-Y gastric bypass (RYGB) surgery (4). Their results showed that genes for glycerolipid syntheses that are directly involved in regulating adipose tissue fat stores were significantly correlated with postoperative body weight loss.…”
Section: Expectations Of Gene Expression Profiling Studiesmentioning
confidence: 99%
See 1 more Smart Citation